TEACHER TRAINING AND INCLUSIVE EDUCATION: THEORETICAL FOUNDATIONS, EDUCATIONAL POLICIES, AND TEACHING PRACTICES (REMUNOM, 2026)
This study analyzes the relationship between teacher training and the implementation of inclusive education, considering its theoretical foundations, its links with educational policies, and its implications for contemporary teaching practices. It is based on the assumption that the consolidation of inclusive education requires the reconfiguration of teacher training processes, both in initial and continuing training, with a view to building educational practices that recognize and value diversity in the school context. Methodologically, this is a qualitative research study, developed through document analysis, literature review, and empirical investigation with education professionals, involving semi-structured interviews and observation of the school context. The results show that, although there have been regulatory advances in the field of public policies aimed at inclusion, gaps remain in teacher training, especially with regard to the articulation between theory and practice and pedagogical preparation to meet the specific educational needs of students. It was also found that inclusive practices depend on continuous training processes, institutional support, and the collective construction of pedagogical knowledge. It can be concluded that the implementation of inclusive education requires the strengthening of teacher training policies, the expansion of differentiated pedagogical strategies, and the consolidation of an educational culture committed to the principles of equity and the right to education for all.